Genetic analysis of a serologically weak D phenotype caused by the p. R191G variant of the RHAG gene - ZHANG Xu; LI Xiaofeng; LI Jianping (Zhongguo shuxue zazhi)
[Objective] To analyze the molecular mechanism of a serologically weak D phenotype caused by RHAG gene variation. [Methods] The full coding and flanking regions of RHD, RHCE and RHAG genes of the serologically weak D phenotype sample were identified through direct sequencing. Bioinformatics software was used to analyze the structure of the variant protein. [Results] The serological test results were weak D and normal Rh Ccee phenotypes. Normal sequence of RHD and RHCE genes, and a homozygous variation c. 572G>A (p. R191Q) of the RHAG gene were revealed by direct sequencing. The c. 572G>A (p. R191Q) mutation was predicted to be “probably damaging”, “deleterious” and “affected” by PolyPhen2, PROVEAN and Mutation Taster algorithms, respectively. The free energy change (△△G) value predicted it to have a destabilizing effect on the RhAG protein. Meanwhile, modeling of the 3D structure predicted that the p. R191Q amino acid substitution may alter the space conformation of the RhAG protein. [Conclusion] A homozygous variation of RHAG gene p. R191Q leads to serologically weak D expression, but does not affect RhCE antigen expression.